An Exploratory Study of the Intention to Use Information Systems to Manage Electricity Consumption: A Theme Analysis of Influencing Factors - Yew, Ming Hock; Cooper, Vanessa (ACIS, 2014)
The value of time feedback on energy consumption, especially with the use of information systems has been demonstrated by much research in this area. What’s lacking in the research, as well as practice, is an understanding of why residents would accept (or reject) the use of IS to manage energy consumption. This paper presents results of an exploratory study, with the use of theme analysis, to understand influencing factors in the adoption of such an IS to manage electricity (the most common form of energy researched) consumption. This led to the conceptualization of a model, based on the Theory of Planned Behaviour that could facilitate further studies to understand the likelihood of intention to adopt an IS to manage electricity consumption. The result of such a study could be used for further empirical studies to explain low adoption rate (or even resistance) in mass implementation of such an IS.